Knowledge, attitudes, and beliefs regarding skin cancer among health sciences students in Turkey: a cross-sectional study - Dogan, Esin Sevgi; Caydam, Ozden Dedeli (São Paulo Medical Journal, 2025)
BACKGROUND: Healthcare professionals’ knowledge, attitudes, and beliefs regarding skin cancer are important for reducing the future impact of the disease. OBJECTIVE: This study evaluated university students’ knowledge, attitudes, and beliefs about skin cancer and examined the variables influencing their attitudes and beliefs about the disease. DESIGN AND SETTING: This descriptive cross-sectional study was conducted at the Faculty of Health Sciences at Manisa Celal Bayar University, Manisa, Turkey. METHOD: A total of 960 students participated in this study. Data were collected using the Student Introduction Form, Fitzpatrick Skin Type Scale, Skin Cancer and Sun Knowledge Scale (SCSKS), and Health Belief Model Scale for Skin Cancer (HBMSSC). RESULTS: The mean SCSKS score of the participants was 14.91 ± 4.23. The mean HBSSC scores of the participants were 23.58 ± 7.79 for perceived susceptibility, 14.79 ± 4.59 for perceived severity, 20.64 ± 6.60 for perceived benefits, 15.93 ± 4.09 for perceived barriers, and 21.78 ± 7.14 for self-efficacy. The mean SCSKS total scores of the university students were significantly and positively correlated with the HBMSSC subdimensions. Gender explained 1.58 of the variance in perceived benefits and 1.65 of the variance in self-efficacy, whereas the SCSKS score explained most other variables. CONCLUSION: The students’ knowledge of skin cancer and sun protection was moderate. Their attitudes and beliefs regarding skin cancer were unexpected. This study identified students’ knowledge of skin cancer and sun protection as the most important variables for improving their attitudes and beliefs about skin cancer.